Pemberdayaan Komunitas Anak Jalanan Terminal Tawang Alun Berbasis Kewirausahaan dan Media Sosial (Entrepreneurship) di Kabupaten Jember - Fadlillah, Fadlillah; Asnawan, Asnawan; Ratnasari, Khurin'In (Auladuna: Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study wants to describe the existence of street children, street children are a group of children who spend their childhood and adolescence selling newspapers, busking, or just asking for mercy from the people they meet to meet their daily needs. Economic difficulties make them not have time to get an education like children in general. Through the empowerment program, street children are given the knowledge to be able to see various business opportunities around them, as well as be creative in utilizing everything around them. The results of this activity include: identifying the target group, exploring the problems of the target group, coordinating the theme of community service activities, preparing for the implementation of activities, implementing activities, and evaluating the activities carried out. Therefore, community service activities for street children through entrepreneurship-based training and social media are very important so that they can develop their potential in being competent and taking advantage of everything around them without having to spend a lot of money. It is hoped that with this training service, the university and the Street Child Development Institute will always provide assistance to street children in providing life skills in developing entrepreneurial potential and expanding product marketing networks through social media.